Synthesis, characterization and fluorescence properties of selected amino derivatives of quinoline / Zainal Abidin Hasan - Zainal Abidin, Hasan (2012)
ii ABSTRACT 2-N-(3-methyl)piperidinoquinoline (25), 2-N-(4-methyl)piperidinoquinoline (26), 2-N-anilinoquinoline (28), 2-N- (m-methyl)anilinoquinoline (30), 2-N-(p-methyl)anilinoquinoline (32), 2-N-(m-ethyl)anilinoquinoline (34), 2-N-(p-ethyl)anilinoquinoline (36), 2-N-methylanilinoquinoline (38), 2-N-ethylanilinoquinoline (40), 2-N-(m-methoxy)anilinoquinoline (42), 2-N-(p-methoxy)anilinoquinoline (44), 2-N-(m-chloro)anilinoquinoline (46), and 2-N-(p-chloro)anilinoquinoline (48) were prepared by reacting 2-chloroquinoline (22) with 3-methylpiperidine (23), 4-methylpiperidine (24), aniline (27), m-toluidine (29), p-toluidine (31), m-ethylaniline (33), p-ethylaniline (35), N-methylaniline (37), N-ethylaniline (39), m-anisidine (41), p-anisidine (43), m-chloroaniline (45) and p-chloroaniline (47) respectively. The structure of these compounds were confirmed using 1H NMR, 13C NMR, infra-red and GCMS. The fluorescence properties were recorded using Luminescence Spectrophotometer. Almost all compounds prepared showed highest fluorescence intensity in less polar solvents and lowest fluorescence intensity in polar protic solvents. Compound 30, 34 and 48 showed higher fluorescence intensity in alkaline and neutral conditions while lower fluorescence intensity was recorded in acidic condition.